Quality of service architectures for wireless networks [ performance metrics and management - Adibi, Sasan , 1970- (Gale virtual reference library, 2010)
"This book further explores various issues and proposed solutions for the provision of Quality of Service (QoS) on the wireless networks" -- Provided by publisher